1993
DOI: 10.1111/j.1524-4725.1993.tb00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Less Painful Alternatives for Local Anesthesia

Abstract: The pH values of bacteriostatic saline solution with epinephrine 1:300,000 and lidocaine with epinephrine diluted with bacteriostatic saline solution are 5.3 and 4.2, respectively. Both were found to be less painful than 1% lidocaine with epinephrine with sodium bicarbonate 84 meq/mL, which had a pH of 7.4. It is unlikely that the pain of infiltration is a simple function of the pH of the anesthetic solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 8 publications
1
17
1
3
Order By: Relevance
“…A significance decrease in pain has also been reported when using a cooled lidocaine gel but this method have not reached widespread acceptance in the urological community [11]. On the other hand, the administration of local anesthetic agents can cause pain in itself [12,13]. In support of this, it has been reported that the delivery of lidocaine gel may cause more discomfort than plain gel.…”
Section: Discussionsupporting
confidence: 51%
“…A significance decrease in pain has also been reported when using a cooled lidocaine gel but this method have not reached widespread acceptance in the urological community [11]. On the other hand, the administration of local anesthetic agents can cause pain in itself [12,13]. In support of this, it has been reported that the delivery of lidocaine gel may cause more discomfort than plain gel.…”
Section: Discussionsupporting
confidence: 51%
“…Unfortunately the anaesthesia is only of very short duration, approximately 2–5 min. This can be prolonged by the use of adrenaline admixture with minimal effect on the pain of infiltration 11 . Unfortunately bacteriostatic saline is not available in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…The onset, duration and quality of the block do not appear to be affected adversely by buffering. Some of the studies assessed this directly by timing for the onset and duration of anaesthesia 5,7,11 . Anaesthesia was usually checked for by loss of pinprick sensation or cold sensation with alcohol swabs.…”
Section: Discussionmentioning
confidence: 99%
“…41 Several studies examined strategies to overcome discomfort during urethral instillation to increase clinical effectiveness of lidocaine gel.…”
Section: Improving Factorsmentioning
confidence: 99%